АНАЛИЗ СОВРЕМЕННОГО СОСТОЯНИЯ АТОМНОЙ ОТРАСЛИ КАЗАХСТАНА - Sarsekeyev, A.B. (Recent Contributions to Physics, 2017)
The article presents the structure of the reactor experimental facilities of the Republic of Kazakhstan. And it also shows the status and prospects of research in the nuclear industry in Kazakhstan in the aspect of world development trends.